Policy and Practice in Bangladesh: Obstacles and Outcomes - Md. Alomgir Hossan; Md. Burhan Uddin Milon (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Policy making and implementation are crucial aspects of governance that significantly impact the socio-economic development of a country like Bangladesh. Over the period from 2009 to 2024, Bangladesh has faced numerous challenges and obstacles in formulating and executing policies effectively. The purpose of this study is to examine the issues and difficulties that Bangladesh faced during this time in developing and implementing policies. We used qualitative research methods to meet our research objectives. In this study, we carefully followed journal articles, newspapers, policy documents, and related books. We examine various factors contributing to these challenges, including political instability, bureaucratic inefficiency, corruption, lack of coordination, inadequate resources, and external influences. The result reveals that the policy could not be successful due to corruption, accountability, transparency, political influence, and the participation of the general people in the policy formulation. Finally, the paper formulated potential solutions and recommendations to address these issues and improve the policy-making process in Bangladesh.